Distributed wireless sensing–based routing and adaptive least–travel–time navigation in VANET. (1st March 2013) - Chang, Ben–Jye; Liang, Ying–Hsin; Huang, Bo–Jhang
Most navigation systems adopt a static shortest path routing algorithm with an optional traffic information gathered from a few monitoring devices and managed by a centralised Traffic Information Centre (TIC). It yields several drawbacks: only offering the partial traffic information and yielding a low reliability because of using a centralised TIC. This paper thus proposes a fully distributed approach, namely the Distributed Wireless sensor network–based Adaptive least–travel–time Navigation approach (D–WAN). In D–WAN, the real–time traffic information is collected from diverse types of sensors equipped on vehicles and exchanged among neighbour vehicles, and then build a fully distributed and reliable navigation environment. Numerical results demonstrate D–WAN outperforms the compared approaches in travel time, exhausted gasoline, and traffic load balancing index while yielding competitive travel distance. The worst case running–time is analysed, which requires O(N · R) and O(M²) time under the high–density and sparse vehicle environments, respectively.